Stepping Back to Move Forward: Assessing the Quality of Maternity Health Services of Kathmandu Valley - Bhetwal, Kiran (Journal of Business and Social Sciences Research, 2018)
This paper is the assessment of the women’s perception towards the quality of services they received during their maternity time and examining their level of satisfaction with the intention to revisit the same hospital for future services. Primary quantitative data through the distribution of questionnaire from 150 respondents using convenience sampling from five hospitals viz Nagarik Hospital, Teaching Hospital, Thapathali Hospital, KMC and Patan Hospital were collected. Majorities of the respondent were satisfied enough to return to the hospital and would happily recommend others as well. This study found that human and physical resources have the lowest average. Implying that most of the respondent felt that it was the most important factor while choosing the hospital followed by privacy, cognition, physical abuse, denial of requested care, confidentiality, emotional support, involvement of family member and finally respect, dignity and equity scores last. It means that no matter which hospital respondent went they found it most obvious to be treated with respect. It clearly shows the reason on why the hospital is investing more on the infrastructure rather than innovating and delivering higher service quality. On the serious note, a case of physical and verbal abuse also came into light during the investigation. Not much of research based policies are seen to protect such critical case.